Design and Validity of Cognitive Conflict-Based Teaching Materials Integrating Virtual Laboratories to Improve Concept Understanding of Waves - Reni Saputri; Fatni Mufit; Gusnedi Gusnedi; Silvi Yulia Sari (Universitas Lambung Mangkurat, 2021)
Learning physics shows that students' understanding of concepts is still low, and there are misconceptions. One solution to overcome this problem is to create conflict-cognitive-based physics teaching materials that integrate virtual laboratories. The purpose of this research was to produce valid cognitive conflict teaching materials. The type of research was development research using the Plomp model. The preliminary research instruments were in the form of concept tests and questionnaires. Meanwhile, a self-evaluation sheet was used at the development stage, and a validation sheet used three validators. The self-evaluation data analysis technique used percentage techniques, while the validity used the Aiken's V formula. At the preliminary research stage, it was found that more than 30% of students experienced misconceptions, and 40% of students did not understand the concept. From questionnaires to teachers, it was found that learning was still teacher-centred, and ICT facilities had not been used optimally. At the development stage, a prototype of teaching materials was designed using the cognitive conflict-based learning model stages. The self-evaluation test results obtained a score of 85, which was categorized as very good, while in the expert review test, the value of all components was 0.81 was categorized as very valid and capable of being tested for practicality and effectiveness tests in learning.